Characterization of the flavor and nutritional value of coconut water vinegar based on metabolomics. (1st February 2022) - Xu, Senzheng; Ma, Zewei; Chen, Ying; Li, Jiaxin; Jiang, Haiyan; Qu, Taiqi; Zhang, Weimin; Li, Congfa; Liu, Sixin
Highlights: The potential value of waste coconut water (mature coconut water) was explored and waste coconut water was produced into high value-added healthy food. Fresh coconut water vinegar showed pungent sour taste, but aged coconut water vinegar showed almond, banana or pear-like aroma. Coconut water vinegar is rich in essential amino acids, especially phenylalanine. 17 key metabolic pathways were found, and 3 key metabolic substrates (aspartate, glutamate and pyruvate) were found, through pathway analysis. Abstract: Tender Coconut water is popular for its deliciousness and nutrition. Mature coconut water, usually discarded as waste in the coconut kernel-based food industry due to its unpleasant flavor, was used as a raw material to make vinegar by liquid-state fermentation. The compounds in fresh coconut water with high odor activity values (OAVs) were isovaleric acid and acetic acid, with pungent sour tastes. The compounds with high OAVs in aged coconut water vinegar were phenylethyl acetate, isoamyl acetate and benzaldehyde, with almond, banana or pear-like aromas. Coconut water vinegar was rich in essential amino acids, especially phenylalanine. Through pathway analysis, seventeen key metabolic pathways and three key metabolic substrates (aspartate, glutamate and pyruvate) were found. According to sensory evaluation, the aged vinegar tastes better. Coconut water vinegar is delicious and nutritious, so reprocessing mature coconut water into vinegar is an appropriate way to reuse waste coconut water.